2015
DOI: 10.1177/1075547015617941
|View full text |Cite
|
Sign up to set email alerts
|

Using Political Efficacy Messages to Increase Climate Activism

Abstract: Using an online experiment with a national sample, this study tests the effects of political efficacy messages on two types of climate-related political participation via the discrete emotions of hope, fear, and anger and compares these effects across ideological groups. Relative to a message that discusses only negative climate impacts, messages that emphasize the internal, external, or response efficacy of political actions to address climate change are found to influence hope and fear but not anger, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
133
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(143 citation statements)
references
References 37 publications
10
133
0
Order By: Relevance
“…Similarly, hope and concern about a changing climate were both linked to pro-environmental behaviour amongst children (Stevenson & Peterson, 2015), suggesting hope is not a denial of the problem, but may rather be grounded in the (uncertain) reality of the situation. Some evidence suggests that efficacy information can increase climate-related political participation via hope (Feldman & Hart, 2016) and that feelings of hope predict support for climate policies (Smith & Leiserowitz, 2014). Yet, some studies have shown that despite achieving an increase in hope with either hopeful (Chadwick, 2015) or optimistic (Hornsey & Fielding, 2016) climate messages, this hope did not translate into an increase in climate-mitigating behavioural intentions.…”
Section: Hope and Collective Actionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, hope and concern about a changing climate were both linked to pro-environmental behaviour amongst children (Stevenson & Peterson, 2015), suggesting hope is not a denial of the problem, but may rather be grounded in the (uncertain) reality of the situation. Some evidence suggests that efficacy information can increase climate-related political participation via hope (Feldman & Hart, 2016) and that feelings of hope predict support for climate policies (Smith & Leiserowitz, 2014). Yet, some studies have shown that despite achieving an increase in hope with either hopeful (Chadwick, 2015) or optimistic (Hornsey & Fielding, 2016) climate messages, this hope did not translate into an increase in climate-mitigating behavioural intentions.…”
Section: Hope and Collective Actionmentioning
confidence: 99%
“…The inconsistent results could be due to the different theoretical approaches to hope in these studies. Some studies lean towards more expectation-based approaches (Ojala, 2015;Stevenson & Peterson, 2015), while others treat hope as a discrete emotion amongst others with minimal theoretical specification (Feldman & Hart, 2016), which makes it difficult to draw firm conclusions about the role of hope.…”
Section: Hope and Collective Actionmentioning
confidence: 99%
“…Importantly, many research designs involve multicategorical variables, such as when an experimenter creates or collects three or more versions of a communication-related stimulus that vary on some manipulated dimension or feature (e.g., Feldman & Hart, 2016;Hurley, Jensen, Weaver, & Dixon, 2015;Niederdeppe, Shapiro, Kim, Bartolo, & Porticella, 2014), or when the effects of communication are measured in people who differ in (for example) ethnicity or political party identification (e.g., Habush, Warren, & Benuto, 2012).…”
mentioning
confidence: 99%
“…Perceived understanding affords citizens a sense of self‐efficacy and, as such, motivates their decision to act upon objective policy understanding (see Bandura ). Accordingly, greater perceived policy understanding plays an important role in translating (latent) policy attitudes that result from objective understanding into shows of policy support or discontent (Zimmerman ; Feldman and Hart ). While objective and perceived understanding can move independently (see Kruger and Dunning ), determinants that positively influence objective understanding tend to also positively influence perceived understanding (Sweller ; Rennekamp ).…”
Section: Transparency and Its Implications For Policy Supportmentioning
confidence: 99%
“…Perceived understanding affords citizens a sense of self-efficacy and, as such, motivates their decision to act upon objective policy understanding (see Bandura 1997). Accordingly, greater perceived policy understanding plays an important role in translating (latent) policy attitudes that result from objective understanding into shows of policy support or discontent (Zimmerman 2000;Feldman and Hart 2016).…”
Section: Policy Understanding: a Mechanism For Engendering Policy Smentioning
confidence: 99%